Sociodemographic profile and hospitalization process of elderly assisted at a emergency hospital - Maria Luciene Nobre Coutinho; Margarita Acevedo Samúdio; Luciene Miranda de Andrade; Rainério Nobre Coutinho; Denise Maia Alves da Silva (Rev Rene)
Objectives: to investigate the sociodemographic profile and the process of hospitalization of elderly assisted in an emergency hospital. Methods: descriptive epidemiological study conducted at an emergency hospital with 300 elderly patients using a form with hospitalization process and sociodemographic variables. Results: there was a predominance of females (56.0%), between 80 and 89 years old (45.4%), illiterate or with elementary education (86.7%), married or living in stable union (42.6%), with non-communicable chronic disease (54.7%) and regular use of medications. The main reason for hospitalization was fall (54.7%) at home and in the morning hours (42.4%), with admission in the afternoon, transported by ambulance. Conclusion: the findings contribute to the development of strategies directed to assist and care of the healthy elderly and in vulnerable situations.